New ecdysteroid and ecdysteroid glycosides from the roots of Serratula chinensis. Issue 3 (4th March 2017) - Zhang, Zi-Yue; Yang, Wei-Qun; Fan, Chun-Lin; Zhao, Hui-Nan; Huang, Xiao-Jun; Wang, Ying; Ye, Wen-Cai
Abstract: Three new ecdysteroid glycosides (1–3 ) and one new ecdysteroid (4 ), were isolated from the roots of Serratula chinensis . Their structures were established on the basis of extensive spectroscopic analysis and chemical methods.